1978
DOI: 10.1530/acta.0.0870535
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Release, Insulin Content, and Glucose Utilization in Isolated Mouse Islets Maintained in Tissue Culture

Abstract: To elucidate the remission phase in juvenile diabetics the insulin release, insulin content, and glucose utilization were measured in isolated Langerhans' islets from mice maintained for 6 days in a tissue culture at a glucose concentration of 278 mmol, followed by a culture period of 4 days at 6.1 mmol glucose. These experiments revealed that the ability of the islets to store and secrete insulin during glucose stimulation decreased considerably during incubation at high concentrations of glucose. When the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…28 -3°- 32 Lacy and Gingerich 33 showed that the acute response to a glucose stimulus (5 g/L) was better preserved in isolated adult islets that had been cultured in 2.5 g/L glucose than in islets maintained in 1 g/L glucose. Eff 34 showed that glucose-stimulated insulin release was higher for cultures of isolated adult mouse islets that had been grown for 6 days at 27.8 mM glucose and then 4 days at 6.1 mM glucose than islets maintained at 6.1 mM glucose for the entire 10 days. Hellerstrom et al 35 showed that islets obtained with mild collagenase digestion of fetal rat pancreata and cultured for 8 days in medium containing 11.1 or 22.2 mM glucose responded to an acute glucose stimulus (16.7 mM) whereas there was no response by islets cultured in 5.5 or 2.8 mM glucose.…”
Section: Discussionmentioning
confidence: 99%
“…28 -3°- 32 Lacy and Gingerich 33 showed that the acute response to a glucose stimulus (5 g/L) was better preserved in isolated adult islets that had been cultured in 2.5 g/L glucose than in islets maintained in 1 g/L glucose. Eff 34 showed that glucose-stimulated insulin release was higher for cultures of isolated adult mouse islets that had been grown for 6 days at 27.8 mM glucose and then 4 days at 6.1 mM glucose than islets maintained at 6.1 mM glucose for the entire 10 days. Hellerstrom et al 35 showed that islets obtained with mild collagenase digestion of fetal rat pancreata and cultured for 8 days in medium containing 11.1 or 22.2 mM glucose responded to an acute glucose stimulus (16.7 mM) whereas there was no response by islets cultured in 5.5 or 2.8 mM glucose.…”
Section: Discussionmentioning
confidence: 99%
“…While direct injection worked well for mouse islet isolation, 40 it had not been effective in our previous attempts in the dog, human, or monkey pancreas and was not further evaluated. Ductal injection had the problems previously described plus the obvious drawback of low islet yields.…”
mentioning
confidence: 99%